Phylogenetic insight into ABCE gene subfamily in plants - Jakobson, Liina; Mõttus, Jelena; Suurväli, Jaanus; Sõmera, Merike; Tarassova, Jemilia; Nigul, Lenne; Smolander, Olli-Pekka; Sarmiento, Cecilia (Frontiers in Genetics, 2024)
ATP-BINDING CASSETTE SUBFAMILY E MEMBER (ABCE) proteins are one of the most conserved proteins across eukaryotes and archaea. Yeast and most animals possess a single ABCE gene encoding the critical translational factor ABCE1. In several plant species, including Arabidopsis thaliana and Oryza sativa, two or more ABCE gene copies have been identified, however information related to plant ABCE gene family is still missing. In this study we retrieved ABCE gene sequences of 76 plant species from public genome databases and comprehensively analyzed them with the reference to Arabidopsis thaliana ABCE2 gene (AtABCE2). Using bioinformatic approach we assessed the conservation and phylogeny of plant ABCEs. In addition, we performed haplotype analysis of AtABCE2 and its paralogue AtABCE1 using genomic sequences of 1135 Arabidopsis thaliana ecotypes. Plant ABCE proteins showed overall high sequence conservation, sharing at least 78% of amino acid sequence identity with AtABCE2. We found that over half of the selected species have two to eight ABCE genes, suggesting that in plants ABCE genes can be classified as a low-copy gene family, rather than a single-copy gene family. The phylogenetic trees of ABCE protein sequences and the corresponding coding sequences demonstrated that Brassicaceae and Poaceae families have independently undergone lineage-specific split of the ancestral ABCE gene. Other plant species have gained ABCE gene copies through more recent duplication events. We also noticed that ploidy level but not ancient whole genome duplications experienced by a species impacts ABCE gene family size. Deeper analysis of AtABCE2 and AtABCE1 from 1135 Arabidopsis thaliana ecotypes revealed four and 35 non-synonymous SNPs, respectively. The lower natural variation in AtABCE compared to AtABCE1 is in consistence with its crucial role for plant viability. Overall, while the sequence of the ABCE protein family is highly conserved in the plant kingdom, many plants have evolved to have more than one copy of this essential translational factor.